2021
DOI: 10.4103/jrms.jrms_661_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of dexmedetomidine and propofol in reducing recovery agitation in pediatric patients after ketamine procedural sedation in emergency department

Abstract: Background: Ketamine has been a safe and effective sedative agent commonly used for painful pediatric procedures in the emergency department (ED). This study aimed to compare the effect of dexmedetomidine (Dex) and propofol when used as co-administration with ketamine on recovery agitation in children who underwent procedural sedation. Materials and Methods: In this prospective, randomized, and double-blind clinical trial, 93 children aged between 3 and 17 years with Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Study designs included 11 RCTs, 22,32–41 13 cohort studies and other nonrandomized studies, 19–21,23,42–50 and 11 case series and case reports 12,51–60 . Six of the included studies were conference abstracts 20,21,40,47,50,56 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study designs included 11 RCTs, 22,32–41 13 cohort studies and other nonrandomized studies, 19–21,23,42–50 and 11 case series and case reports 12,51–60 . Six of the included studies were conference abstracts 20,21,40,47,50,56 .…”
Section: Resultsmentioning
confidence: 99%
“…Three trials identified higher rates of adverse events with DEX than with the various pharmacologic comparators. One trial 33 identified higher rates of hypotension with DEX (22.6% with ketamine plus DEX as opposed to 6.5% with ketamine plus propofol or 0% with ketamine alone). Another trial 34 found higher rates of need for supplemental oxygen or airway maneuvers with ketamine plus DEX than with ketamine plus propofol or ketamine alone, and a third trial found higher incidence of transient bradycardia with DEX plus fentanyl (three cases, 8%) than with midazolam plus fentanyl (no cases, 0%) 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Contrastingly, dexmedetomidine is known to cause bradycardia and hypotension. 19,20 Mason et al showed reductions in BP and transient bradycardia in a subset of patients injected with dexmedetomidine, and a recent metaanalysis showed a dose-dependent reduction in heart rate in the dexmedetomidine group. 7,14 Ketamine can reverse dexmedetomidine-induced bradycardia and hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Tosun et al revealed that HR was significantly higher in the Ketadex group than in the Ketofol group (28). Azizkhani et al showed that the mean of PR, MAP, and SpO 2 was not significantly different between the Ketadex and Ketofol groups (10).…”
Section: Discussionmentioning
confidence: 99%